Queer Enclaves: Warsaw Clubs in the Early 2000s - Rita Müller (InterAlia, 2022)
In this paper, I analyze selected art shows, that took place in Warsaw clubs (Le Madame and M25) in the early 2000s. I describe the performances of the art collective Suka Off and the play “Miss HIV” directed by Maciej Kowalewski, as well as the reception of these shows. Described actions boldly and innovatively addressed issues of human carnality and non-normative sexuality. In the article, I attempt to include these performances in a local queer history – while trying to analyze the story (which I produce) critically.